PENGENALAN ISO 31OOO: INTERNATIONAL RISK MANAGEMENT STANDARDS - Rosita Widjojo (Bina Ekonomi, 2008)
Risk management is becoming an important issue in companies. Therefore, the ISO recognized the need to establish a standard for risk management, which is still in the process of approval from all ISO members, and will be published by the end of 2008 or early 2009 after a consensus has been reached. ISO standards provide requirements or give guidance on good management practice.  ISO 31000 for  international Risk Management  Standards  is considered  as a generic management system standard, which means  that the same standard can be applied  to any organization,  large or small, whatever its product or service,  in any sector of activity, and whether  it is a business enterprise, a public administration,  or a government  department.  The objective of this article focuses on the introduction of ISO 31000 and the framework, to give a brief description of how risk management can be applied in organizations. Organizations with a  commitment  to managing risk know that implementing  standards  can enable  them to do so more effectively  and therefore  maximize  opportunities  and minimize  losses in the course of achieving corporate objectives.